2018
DOI: 10.1002/brb3.963
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive behavioral therapy on resting‐state functional brain network in drug‐naive patients with obsessive–compulsive disorder

Abstract: ObjectivesAlthough cognitive behavioral therapy (CBT) is an effective treatment for obsessive–compulsive disorder (OCD), the treatment mechanisms remain poorly understood. This study aimed to investigate the effects of CBT on changes in the intrinsic whole‐brain functional network of OCD patients.Materials and MethodsTwenty drug‐naive and noncomorbid OCD patients were recruited, and resting‐state functional magnetic resonance imaging was performed before and after 12 weeks of CBT. Moreover, 20 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…This was particularly seen in the somatomotor subnetwork, including its clustering coefficient and variation in efficiency. Similar findings in global and regional measures have been found in healthy controls of previous treatment studies (Li et al, 2018; D. J. Shin et al, 2014), as well as in a study consisting of many time points in a single person (Poldrack et al, 2015).…”
Section: Changes In Functional Network Structure As An Early Marker Osupporting
confidence: 82%
“…This was particularly seen in the somatomotor subnetwork, including its clustering coefficient and variation in efficiency. Similar findings in global and regional measures have been found in healthy controls of previous treatment studies (Li et al, 2018; D. J. Shin et al, 2014), as well as in a study consisting of many time points in a single person (Poldrack et al, 2015).…”
Section: Changes In Functional Network Structure As An Early Marker Osupporting
confidence: 82%
“…Interestingly, meta-analytic findings suggest functional hypoconnectivity between the DMN and task-positive networks in OCD (41). In addition, EX/RP normalizes hypoconnectivity between cognitive control and DMN regions (42), and those prior findings were interpreted as helping patients move from internally focused intrusive thoughts to externally focused attentional processes. Together, these findings suggest DMN function may be a critical marker for EX/RP response.…”
Section: Discussionmentioning
confidence: 96%
“…[89] Studies investigating fMRI changes post-CBT have found improved connectivity between the cerebellum and widespread areas in the caudate, putamen, frontopolar cortex, DLPFC, and VLPFC[115] and normalization of increased left DLPFC and right OFC connectivity. [116] Predictors of improvement following CBT included baseline decreased basolateral amygdala (BLA)-VMPFC functional connectivity. [105]…”
Section: Functional Imagingmentioning
confidence: 99%